RNA aptamers binding the double-stranded RNA-binding domain. - Hallegger, M; Taschner, A; Jantsch, M (2006)
Specific RNA recognition of proteins containing the double-strand RNA-binding domain (dsRBD) is essential for several biological pathways such as ADAR-mediated adenosine deamination, localization of RNAs by Staufen, or RNA cleavage by RNAse III. Structural analysis has demonstrated the lack of base-specific interactions of dsRBDs with either a perfect RNA duplex or an RNA hairpin. We therefore asked whether in vitro selections performed in parallel with individual dsRBDs could yield RNAs that are specifically recognized by the dsRBD on which they were selected . To this end, SELEX experiments were performed using either the second dsRBD of the RNA-editing enzyme ADAR1 or the second dsRBD of Xlrbpa, a homolog of TRBP that is involved in RISC formation. Several RNA families with high binding capacities for dsRBDs were isolated from either SELEX experiment, but no discrimination of these RNAs by different dsRBDs could be detected. The selected RNAs are highly structured, and binding regions map to two neighboring stem-loops that presumably form stacked helices and are interrupted by mismatches and bulges. Despite the lack of selective binding of SELEX RNAs to individual dsRBDS, selected RNAs can efficiently interfere with RNA editing in vivo.